A systematic review and meta‐analysis on the incidence of osteoporosis and fractures after liver transplant. (19th May 2021) - Lim, Wen Hui; Ng, Cheng Han; Ow, Zachariah Gene Wing; Ho, Owen Tsung Wen; Tay, Phoebe Wen Lin; Wong, Keng Lin; Tan, Eunice Xiang Xuan; Tang, Si Ying; Teo, Claire Min‐Li; Muthiah, Mark D.
Summary: Following liver transplant (LT), osteoporosis is a severe complication that causes morbidity. However, the incidence and risk factors of osteoporosis and fractures have not been well described. Single‐arm meta‐analysis of studies reporting osteopenia, osteoporosis, and fractures post‐LT was performed with meta‐regression for study period. Dichotomous variables, continuous variables and time‐to‐event variables were pooled in odds ratio, weighted mean difference and hazard ratio, respectively. For risk factors with limited data, a systematic review of literature was conducted. There was a significant increase in both osteoporosis and fractures compared to non‐LT patients. Osteopenia, osteoporosis and incident fractures were newly diagnosed in 34.53% (CI: 0.17–0.56, n = 301), 11.68% (CI: 0.05–0.24, n = 1251) and 20.40% (CI: 0.13–0.30, n = 4322) of LT patients, respectively. Female gender ( P = 0.017) increased risks of osteoporosis but not older age and BMI. Older age, lower pre‐LT bone mineral density (BMD), presence of bone disease pre‐LT were significant risk factors for fractures but not female gender, post‐menopausal state, BMI, smoking and alcohol. There is a high incidence of skeletal complications post‐LT. Older age, lower pre‐LT BMD and presence of bone disease pre‐LT are significant risk factors that are associated with incident fractures physicians should be cognisant of in liver transplant recipients.